Κατάλογος Έκθεσης Casts of an Island 2024 - Pericleous, Vicky (My University, 2024)
This exhibition marks a pivotal transformation of an old industrial building on the Limassol waterfront into a public space. The Carob Warehouse is one of the most significant modernist structures in Cyprus. It was built in 1960 by local engineer Andreas Papadopoulos and architect Fivos Polidorides and is located between Limassol Marina and the New Port. The PSI Foundation is being created there to secure and renovate this marvel of Cypriot architecture and to propose a strong program to celebrate its conversion into a major cultural venue. The PSI Foundation invited collector and curator Nicos Chr. Pattichis to conceive the very first exhibition on its premises. The exhibition deals with Cypriot Contemporary Art and hosts 43 artists with over 120 works from the last 35 years. Several of the artworks, notably political in nature, date back to after the checkpoints opened in 2004, with new additions and creations inspired by the exhibition. The exhibition highlights a tumultuous historical era for Cyprus during the last 50 years and commemorates the tragedy of 1974 when the Turkish invasion was followed by the division of the island. This period was marked by numerous efforts toward healing and societal restructuring amidst significant global upheavals. The artistic expressions evoked by Nicos Chr. Pattichis covers a broad spectrum of proposals that range from varied painting techniques, constructions, installations, and videos, all representing facets of creative endeavour relating to the unity of universal culture. The artworks featured are curious accumulations of diverse materials, transformations of archival substances and everyday objects with reimagined aesthetic roles, along with new mappings between fictive urban planning and psychogeography. This creative polyphony naturally leads to deep reflections on critical issues tied to historical memory and social progress across all sectors of ‘real’ life, fostering the development of new thinking aimed at building a redemptive worldview. Many of the works are part of the non-profit organisation CYCO (Cyprus Contemporary Art Center). The exhibition takes its title from the monumental installation, ‘Casts of an Island 2024’ by Socrates Socratous, which can be described as ‘the casts or more precisely, the imprints of the island’ of Cyprus. The design and the curator’s theoretical approach create a narrative arc through a sequence of thoughts and ideas, forming thematic units and dialogues among the works. This method constructs an essay-like approach with clear allusions to both the history and national imagination of Cyprus. Thalea Stefanidou, Art Historian
Studies for a Place, The House of Leda, 2023 (video duration: 11’:46’’), video
The Tail of the Image, 2020, Vicky Pericleous, (video duration:08’:13’’)
Keywords: Arts; Exhibitions/Publications; Casts of an Island; Construction of notions of Place; Mnemonics of Space; Historicity; Cultural Geographies; Cultural Imaginaries